Black start: the risk of grid failure from a cyber attack and the policies needed to prepare for it. Issue 2 (2nd April 2020) - Monarch, Benjamin
Abstract : Industries and governments across the world are confronting an ever-growing wave of cyber attacks. Few industries are as vulnerable to these attacks, while simultaneously being indispensible to modern life, as public utilities. Among public utilities the electric grid ranks supreme in its importance to everyday activities, and yet it is under daily siege by actors aiming to cripple it. Should a grid attack of significant magnitude come to fruition, the effects could be devastating and vast. Accordingly, this issue demands immediate attention. This article highlights the urgent nature of this challenge and makes recommendations that should go into effect immediately as a means to mitigate large-scale disruption of the electric grid.